Analysis of iron loss and complex permeability spectra for transverse-field-annealed Fe-based nanocrystalline core - Yuya Tomita; Takeshi Ogasawara; Hiroyuki Takabayashi; Takahiko Iriyama (AIP Advances)
Along with the increase of the operating frequency for power electronic devices, more and more development of higher-performance soft magnetic material with low iron loss and high permeability at high frequency will be expected. In this study, dynamic magnetic domain observation of Fe-based nanocrystalline core with a transverse-field-annealing (TFA) as well as the measurement of its soft-magnetic properties was conducted. The magnetic domain observation revealed that the magnetization process at the frequency below 80 kHz was controlled by domain wall propagation combined with coherent rotation (combined-DWP+CR). We tried to adopt Cole–Cole diagram for the analysis of the iron loss and complex permeability spectra in reversible process below 80 kHz and consequently found that the permeability spectrum coincided with the calculated value by the Cole–Cole type relaxation equation. It was also shown that the iron loss Pc depends on the parameter ϵ (Pc ∝ f1+ϵ), which corresponds to the dispersion of the relaxation frequency.